The Role of the Men Opposed to Violence Against Women Everywhere (MOVE) Program in Addressing Violence Against Women: An Impact Study in Quezon City - Julian, Brayan Jay I.; Lagasca, Matthew Werner L.; Malang, Bernandino P.; Malang, Jocelyn DS. (Future Science / FSH-PH Publications, 2026)
Violence Against Women (VAW) is a very widespread problem with no age, cultural, or socioeconomic limitations. Under the Republic Act No. 9262, VAW encompasses psychological, sexual, physical, and economic abuse among intimate relations, dating relations, or between the persons that share a common child. In response to this, the Quezon City organized the Men Opposed to Violence Against Women Everywhere (MOVE) Program that involved using men as a gender equality agent. This paper evaluated the effect of MOVE on awareness, attitudes, behavior, and community involvement of men on VAW. In a mixed-methods approach, 162 subjects were interviewed in MOVE sub-chapters in Quezon City Hall. Quantitative outcomes revealed an awareness increase of 35.1 in the form of VAW calculated between the mean scores before and after the program. The best outcomes were in learning about survivor support services and such concepts like toxic masculinity. Attitudinally, the participants strongly opposed violence, as they agreed that they should never hit their partner. There was also a high level of involvement in the program, 60.9% of the respondents said they were actively participating and working to revive the MOVE Quezon City Hall chapter. In spite of these gains, there are still challenges, such as the lack of community support and continued interest which can be an obstacle to the greater inclusion of males in the prevention of VAW.